IMPLEMENTATION OF NADHIR ONLINE REGISTRATION SYSTEM IN BADAN WAKAF INDONESIA USING AGILE DEVELOPMENT METHODS - Muhammad Chamdani Sukron; Rizqi Putri Nourma Budiarti; Ahmad Syafiq Kamil (Unusa Press, 2020)
The Indonesian Waqf Board is an independent state institution formed under law number 41 of 2004 concerning endowments. At present, nadhir registration service activities at the Indonesian Waqf Board are still carried out offline, which causes nadhir registration service activities to be inefficient and take a long time. From the above problems the authors make research